Fostering Cultural Connections: A Study of Baubau City and Seoul's Cultural Diplomacy Strategies in Sister City Collaboration 2015-2022 - Aydil Safitri (Indonesian Perspective, 2024)
Baubau City and Seoul are two cities that have established Sister City cooperation. The cooperation has resulted in various programs and activities in the fields of economy, education, technology, and culture. One of the main focuses of this Sister City cooperation is the development of culture, which is considered essential in promoting and strengthening the relationship between the two cities. This article aims to analyze the strategies of the local governments of Baubau City and Seoul in fulfilling the interests of their respective regions through Sister City cooperation. This descriptive-analytical study uses a qualitative approach, presented using secondary data obtained from books, journals, websites, reports, and other sources. By using the concepts of para-diplomacy and Sister City, it is found that cultural development strategies are implemented through various programs and activities such as language and script training, as well as cooperation in the field of education. The results of this research can provide an overview of cultural development strategies in Sister City cooperation, which can serve as a reference for other cities in promoting and strengthening international relationships through cultural development.